1992
DOI: 10.3109/15563659208994443
|View full text |Cite
|
Sign up to set email alerts
|

Ibuprofen Overdose in Adults

Abstract: A prospective study of 63 ibuprofen overdose cases in adults (14 years or older) reported to the Rocky Mountain Poison and Drug Center between March 1987 and February 1988 was done to determine the incidence of renal injury and utility of timed plasma levels. No serious toxicity was noted. No CNS or other significant toxicity was seen with ingestion of less than 3 g. Two patients with normal serum creatinines had minor elevations of the blood urea nitrogen after ingesting 4 and 4.8 g. Timed plasma levels (125 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…A good analysis should use a weight-adjusted dose, but most case reports do not include the patient's weight-making it impossible to verify the accuracy of reported doses. The lowest reported ibuprofen ingestion that produced CNS depression was 3 grams, but neither the age of the patient nor a serum ibuprofen concentration were reported [18]. Pediatric data suggests that ingestions reported as less than 100 mg/kg result in little or no symptoms, while ingestions reported as greater than 400 mg/kg are associated with the development of symptoms [17].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…A good analysis should use a weight-adjusted dose, but most case reports do not include the patient's weight-making it impossible to verify the accuracy of reported doses. The lowest reported ibuprofen ingestion that produced CNS depression was 3 grams, but neither the age of the patient nor a serum ibuprofen concentration were reported [18]. Pediatric data suggests that ingestions reported as less than 100 mg/kg result in little or no symptoms, while ingestions reported as greater than 400 mg/kg are associated with the development of symptoms [17].…”
Section: Discussionmentioning
confidence: 94%
“…For example, a 16-year-old boy had a serum ibuprofen concentration of 160 µg/mL 7 hours postingestion, and he presented with unresponsiveness, hypothermia, and metabolic acidosis [19]. In contrast, a group of 22 ibuprofenoverdose patients who had serum ibuprofen levels ranging from 4 to 750 µg/mL did not develop any severe or life-threatening toxicity [18]. In an attempt to correlate serum level with toxicity, an ibuprofen nomogram was constructed, but its utility is extremely limited and its use not recommended [17].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, 24% of patients in their series reported ingesting at least one drug other than ibuprofen. Symptoms typically occurred within 4 hrs of ingestion, although reports exist of symptomatic adults with renal failure who had onset of their symptoms up to 48 hrs after ingestion (3)(4)(5). Overall, the medical literature contains few reports of severe symptoms following isolated ibuprofen ingestion; only 23 reports of coma and six reports of death currently exist.…”
Section: Discussionmentioning
confidence: 88%
“…Although significant symptoms are rare, several authors have examined whether larger ingestions or higher serum ibuprofen levels can predict symptom severity. Hall et al (3,5) reported a statistically significant association between ingestion of Ͼ440 mg/kg and symptom development in pediatric patients. Based on adult and pediatric ibuprofen levels after ingestions, the authors constructed and later revised an ibuprofen nomogram designed to predict toxicity.…”
Section: Discussionmentioning
confidence: 98%
“…Although serum levels of ibuprofen may be obtained, results are not timely and do not correlate with symptoms or prognosis, thereby limiting its clinical utility in the acute setting. 24,[42][43][44][45] In small ingestions (<100 mg/kg of ibuprofen) without symptoms or with resolution of mild symptoms, no routine testing is recommended. In large ingestions (>400 mg/kg of ibuprofen in a child or 6 g in an adult) or significant symptoms, laboratory studies including blood glucose, electrolytes, blood urea nitrogen, creatinine, and complete cell count are recommended.…”
Section: Diagnosis and Evaluationmentioning
confidence: 98%